2017
DOI: 10.1002/2327-6924.12461
|View full text |Cite
|
Sign up to set email alerts
|

Nurse practitioner perceptions of barriers and facilitators in providing health care for deaf American Sign Language users

Abstract: Background and purpose Nurse practitioners (NPs), as well as all healthcare clinicians, have a legal and ethical responsibility to provide health care for deaf American Sign Language (ASL) users equal to that of other patients, including effective communication, autonomy, and confidentiality. However, very little is known about the feasibility to provide equitable health care. The purpose of this study was to examine NP perceptions of barriers and facilitators in providing health care for deaf ASL users. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
18

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 7 publications
0
21
0
18
Order By: Relevance
“…We selected the socioecological model for its utility in conceptualizing the multilevel determinants of access or use, a utility that has been demonstrated across a wide breadth of literature . From a socioecological perspective, individuals are embedded within larger systems in which multiple levels of influence interact and mutually reinforce one another.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected the socioecological model for its utility in conceptualizing the multilevel determinants of access or use, a utility that has been demonstrated across a wide breadth of literature . From a socioecological perspective, individuals are embedded within larger systems in which multiple levels of influence interact and mutually reinforce one another.…”
Section: Methodsmentioning
confidence: 99%
“…We selected the socioecological model for its utility in conceptualizing the multilevel determinants of access or use, a utility that has been demonstrated across a wide breadth of literature. [23][24][25][26] From a socioecological perspective, individuals are embedded within larger systems in which multiple levels of influence interact and mutually reinforce one another. For example, an individual's use of PPC services is influenced by factors beyond those occurring at the individual level; likewise, individuals' perceptions and practices can perpetuate what occurs at a broader level.…”
Section: Terms For Cancermentioning
confidence: 99%
“…One cannot emphasize enough the importance of everyone's equal possibility within social interactions to avoid communication barriers in healthcare for patients who need other kinds of communication methods than speech [25]. A US study [26] demonstrated the awareness for equal health care for sign language users through more efficient communication without language barriers using professional sign language interpreters.…”
Section: The Study Populationmentioning
confidence: 99%
“…A ausência de um intérprete de LS, especialmente em contextos que englobam questões jurídicas complexas (abordagem policial, sessões dos tribunais), pode comprometer o desenrolar do processo e a segurança e fidedignidade das informações compartilhadas (SCHWARTZ; ELDER, 2018). O mesmo ocorre nos serviços de saúdeos prestadores podem interpretar a lei conforme seu entendimento, gerando possibilidade de erro no diagnóstico e tratamento do paciente (PENDERGRASS et al, 2017).…”
Section: Barreiras Programáticasunclassified